Evaluation of the effectiveness of subcutaneous pollen weed polen allergens - L. Yu. Barycheva; L. V. Dushina; S. S. Masalskiy (Аллергология и Иммунология в Педиатрии)
Background. In European countries, the prevalence of pollen sensitization reaches 30–40%. In Russia pollen allergy ranges from 12,7 to 38 %. In the southern regions the main one is ragweed and weed pollen. The efficacy of the subcutaneous medicinal ragweed allergen has not previously been evaluated using modern symptom scales.   Methods. Open-label, single-center, placebo-uncontrolled study of 60 patients aged 16–55 years with allergic rhinitis in combination with bronchial asthma and without it. A 2-preseason course of AIT with a subcutaneous allergen of Ambrosia was used for patients with monosensitization and an allergen Ambrosia + Artemisia (for oligosensitized patients) and Ambrosia + a mix of pollen of causal allergen for polysensitized patients. Treatment started 4 months before and stopped 2–4 weeks before the beginning of pollination. The RTSS (Rhinoconjunctivitis total symptom score) scale was used to assess the symptoms, and the DMS (Daily medical score) was used to estimate of medical treatment.   Results. After 1-st season of treatment, there was a rapid decrease in the RTSS to 5,0 [4,0; 9,0] compared to the initial values of 13 [10, 15] points. By the second year, the decline in RTSS amounted to 4,5 [3,0; 4,5] points (p < 0,001), the total effect size by second year was 0,96 (strong effect of the intervention). DMS (before treatment) was 2,0 [2,0; 2,0] points, after the first and second years — 1,0 [1,0; 2,0] points (p = 0,002), with a moderate effect size of 0,67 after the first year; by the second year, the effect size is 0,75 versus baseline (p < 0,01).   Conclusion. Monotherapy with a subcutaneous ragweed allergen or its combination with other allergens show high effectiveness, starting from the first year of therapy. In the second year, the improvement continues, but the dynamics decreases. The study demonstrated a strong size of the effect of medical intervention, which cannot be explained by the placebo effect.